DESIGN AND BUILD ONLINE SHOP SENTRA UKM MERR SURABAYA - Rahardjo, Cefa; Sunarto, Dewiyani; Tanuwijaya, Haryanto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Sentra UKM MERR Surabaya is an icon symbolic for Usaha Kecil Menengah (UKM) which is built in Surabaya. Sentra UKM MERR Surabaya currently experiencing problems with the stock record which still using stock card to record the stock so that mistakes still happen and also the transactions such as sales report, best seller UKM, best selling item, products report, customer report, ukm report and stock mutation report that doesn’t work well. On the other hand the promotions of the products also doesn’t work really well, we can see it from the visitor that only approximately 50 people. The solutions that given is build an online shop that can manage sales transactions, give more actual data about the stock product and helps promoting the products. Besides that, it also facilitate communication between Sentra UKM MERR Surabaya, UKM and customers. This online shop can help administration to manage the sold product without the stock card and this application can generate reports such as sales report, best seller UKM, best selling item, products report, customer report, ukm report and stock mutation report. Based on the results of user evaluation obtained value 67,5% that stands for very good and 32,5% stands for good.